2018
DOI: 10.15294/jda.v9i1.12001
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Agency and Institutional Theory in the Planning and Realization for Capital Expenditures

Abstract: The capital expenditures are part of direct expenditure in the regional budget. The other elements of capital expenditures are: personnel expenditure, and spending on goods and services. Planning and realization for capital expenditure in the regional budget for each Government Regional Work Units is a part of policy regional financial management in fiscal decentralization policy which need be increased to achieve value significantly over time. Increasing in planning and realization of capital expenditures is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The result showed that the banking sector in China have consistent result in both methods. As noted by Hifni (2017), a well-functioning public expenditure management system (PEM) is considered a critical pillar of government efficiency. The study discusses public expenditure management systems in developing countries based on an analytical framework on principal-agent theory and allows for associations between institutional settings.…”
Section: Efficiency Measurement Model and Input Output Relationship In Measuring Efficiencymentioning
confidence: 99%
“…The result showed that the banking sector in China have consistent result in both methods. As noted by Hifni (2017), a well-functioning public expenditure management system (PEM) is considered a critical pillar of government efficiency. The study discusses public expenditure management systems in developing countries based on an analytical framework on principal-agent theory and allows for associations between institutional settings.…”
Section: Efficiency Measurement Model and Input Output Relationship In Measuring Efficiencymentioning
confidence: 99%